2015
DOI: 10.9755/ejfa.v27i2.19288
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chitosan coating on quality and nutritional value of fresh-cut and #8216;Rocha and #8217; pear

Abstract: One of the greatest barriers to the commercial marketing of fresh-cut fruit is limited shelf-life due to tissue softening and surface browning. Moreover, the development of microorganisms on the fruit surface can compromise the safety of the fresh-cut product. Edible coatings have been proposed as postharvest treatments to maintain quality and prolong shelf-life. The present work aims to evaluate the effect of chitosan coatings in physical, chemical, nutritional and microbiological characteristics of minimally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
8
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
6
8
1
Order By: Relevance
“…For the pulp, the a* and b* values ranged from −11.07 to 2.25 and 8.15 to 17.68, respectively. Similar color values for Rocha pear pulp were reported in other studies [ 27 , 28 ]. The a* and b* values of peel are considered good indicators to measure the influence of storage conditions [ 27 ], presenting values able to diagnose the storage of the fruits.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…For the pulp, the a* and b* values ranged from −11.07 to 2.25 and 8.15 to 17.68, respectively. Similar color values for Rocha pear pulp were reported in other studies [ 27 , 28 ]. The a* and b* values of peel are considered good indicators to measure the influence of storage conditions [ 27 ], presenting values able to diagnose the storage of the fruits.…”
Section: Resultssupporting
confidence: 89%
“…This index ranged from 37.24 to 141.11. The TSS and TA values observed in this work were similar to those reported for the “Pera Rocha do Oeste” pear [ 8 , 28 ], as well as those for Bartlett pear [ 30 ] and a Pyrus communis L. variety.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…There is no statistical difference between storage end values of CH and CHS coated samples (P >0.05). Sánchez et al (2015) reported that the decrease in hue angle showed a similar tendency in all treatments, and after 10 days, they observed only a slight difference between control and chitosan coated pear slices. In addition, similar effects of chitosan were observed in color preservation of fresh cut fruits such as strawberry, papaya, peach, pear, kiwi and mango (Du et al, 1997;Chien et al, 2007;Campaniello et al, 2008;Gonzalez-Aguilar et al, 2008).…”
Section: Resultsmentioning
confidence: 78%